Marine heatwaves as selective filters on the behaviour of native and non-native invertebrates - Sara Ferretti; Armando Macali; Valeria Mazza; Claudio Carere (Biological Invasions, 2025)

Cryptic biodiversity in the commercial diamondback squid Thysanoteuthis rhombus Troschel 1857 - Diego Deville; Souta Mori; Kentaro Kawai; Alejandro Escánez; Armando Macali; Fedor Lishchenko; Heather Braid; Jean Githaiga-Mwicigi; Kolliyil S. Mohamed; Kathrin S. R. Bolstad; Kazutaka Miyahara; Chikatoshi Sugimoto; et al. (Reviews in Fish Biology and Fisheries, 2024)

Cannibalism, self-cannibalism and autotomy in the non-indigenous nudibranch Godiva quadricolor - Armando Macali; Sara Ferretti; Serena Scozzafava; Claudio Carere (Rendiconti Lincei. Scienze Fisiche e Naturali, 2023)

Pioneer settlement of the cold-water coral Desmophyllum dianthus (Esper, 1794) on plastic - Elisa Bergami; Erik Caroselli; Lisa Vaccari; Ilaria Corsi; Alexander Semenov; Armando Macali (Coral Reefs, 2021)
Larval settlement is a critical step for sessile benthic species such as corals, whose ability to thrive on diverse natural and anthropogenic substrates may lead to a competitive advantage in the colonization of new environments with respect to a narrow tolerance for a specific kind of substratum. Plastic debris, widespread in marine waters, provides a large, motile, and solid substratum supporting a highly diverse biological community. Here we present the first observation of a floating plastic bottle colonized by the deep-sea coral Desmophyllum dianthus . The density pattern and co-occurring species composition suggest a pioneer behavior of this coral species, whose peculiar morphologic plasticity response when interacting with the plastic substrate (i.e., low density polyethylene) has not been observed before. The tolerance of D. dianthus for such plastic substrate may affect ecological processes in deep water environments, disrupting interspecific substrate competition in the benthic community.

Relative Influence of Environmental Factors on Biodiversity and Behavioural Traits of a Rare Mesopelagic Fish, Trachipterus trachypterus (Gmelin, 1789), in a Continental Shelf Front of the Mediterranean Sea - Armando Macali; Alexander Semenov; Francesco Paladini de Mendoza; Alessia Dinoi; Elisa Bergami; Francesco Tiralongo (Journal of Marine Science and Engineering, 2020)
Coastal environments can be influenced by water body masses with particular physical, chemical, and biological properties that create favourable conditions for the development of unique planktonic communities. In this study, we investigated a continental shelf front at Ponza Island (Tyrrhenian Sea) and discussed its diversity and complexity in relation to major environmental parameters. Moon phase and current direction were found to play a significant role in shaping species abundance and behaviour. During in situ observations, we also provided the first data on the behaviour of juveniles of a rare mesopelagic species, Trachipterus trachypterus, suggesting the occurrence of Batesian mimicry.

New Mediterranean Biodiversity Records 2019 - BRANCO DRAGIČEVIĆ; OLGA ANADOLI; DROR ANGEL; MOULOUD BENABDI; GHAZI BITAR; LUCA CASTRIOTA; FABIO CROCETTA; ALAN DEIDUN; JAKOV DULČIĆ; DOR EDELIST; VASILIS GEROVASILEIOU; SALVATORE GIACOBBE; et al. (Mediterranean Marine Science, 2019)
This paper is a collection of novel distributional records of 20 species belonging to 8 phyla (Chlorophyta, Rhodophyta, Cnidaria, Ctenophora, Annelida, Mollusca, Arthropoda and Chordata) from 11 Mediterranean countries, namely, Spain: an additional record of the Canary dentex Dentex canariensis is reported from Spain (Valencia), this is the northernmost record of this species in the Mediterranean; Algeria: the first documented record of Caulerpa chemnitzia is reported from the Algerian coast; France: the first record of the Spotted sea hare Aplysia dactylomela is reported from the eastern coast of Corsica; Italy: the first records of the Lessepsian polychaete Dorvillea similis and the alien bivalve Isognomon legumen are reported from Italian waters while additional records of Mnemiopsis leidyi in the south Adriatic are provided; Libya: the first record of an alien mollusc Crepidula fornicata is reported from Libyan waters; Malta: multiple sightings of gelatinous species Apolemia uvaria, Phacellophora camtschatica and Physophora hydrostatica are reported for the first time from Maltese waters, as well as the first tentative record of the Orange-spotted grouper Epinephelus cfr. coioides; Greece: an occurrence of a rare Bigeye thresher shark Alopias superciliosus is reported from Hellenic Ionian waters, while the first records of the alien Mertens’ prawn-goby Vanderhorstia mertensi, the recently described cyclopoid copepod Oithona davisae and the alien red seaweed Asparagopsis armata are reported from the Aegean Sea. The presence of the micromollusc Euthymella colzumensis is confirmed for Greece; Cyprus: the first record of the red cornetfish Fistularia petimba is reported from Cyprus; Turkey: the first record of the alien jellyfish Marivagia stellata is reported from south-eastern Turkey; Israel: the first records of the sea nettle Chrysaora sp. in the Levant are reported.

New Mediterranean Biodiversity Records (July 2018) - NIKI CHARTOSIA; DIMITRIS ANASTASIADIS; HOCEIN BAZAIRI; FABIO CROCETTA; ALAN DEIDUN; MARIJA DESPALATOVIĆ; VINCENZO DI MARTINO; NIKOS DIMITRIOU; BRANKO DRAGIČEVIĆ; JAKOV DULČIĆ; FURKAN DURUCAN; DENIZ HASBEK; et al. (Mediterranean Marine Science, 2018)
In the present article, new records are given for 15 species (4 native and 9 alien and 2 cryptogenic), belonging to 6 Phyla (i.e. Chlorophyta, Ctenophora, Cnidaria, Mollusca, Arthropoda, and Chordata), from 10 Mediterranean countries: Morocco: the finding of the crab Callinectes sapidus represents the westernmost one of the species in the Mediterranean; Italy: first records of the nudibranch Polycera hedgpethi from the harbour of La Spezia, and first finding of the invasive ctenophore Mnemiopsis leidyi in the Fiora River; Tunisia: Caulerpa taxifolia var. distichophylla is recorded for the first time, showing an even wider distribution in the Mediterranean; Greece: the finding of the jellyfish Pelagia benovici represents the first record of the species in the Ionian Sea, while the finding of the smallscale codlet Bregmaceros nectabanus in the Ionian Sea is another interesting first report for the area; Malta: the cryptogenic scleractinian coral Oculina patagonica was recorded; Slovenia: the parasitic copepod Demoleus heptapus was recorded from a sixgill bluntnose shark, Hexanchus griseus; Croatia: the Lessepsian cephalaspidean mollusc Haminoea cyanomarginata is recorded for the first time from the area; Bulgaria: the Asian date mussel Arcuatula senhousia was recorded from the Black Sea; Cyprus: the Lessepsian gastropod Viriola sp. [cf. corrugata) was recorded for the first time from the area, while two decapod species were recorded also for the first time from Cyprus, i.e. the caridean shrimp Pasiphaea sivado and the anomuran Munida curvimana; Turkey: the acari Lohmannella falcata is recorded for the first time from Antalya and the Lessepsian fish Priacanthus sagittarius in the Levantine coasts of Turkey (off Hatay/Arsuz) showing that this species has extended its range in a very short time.